2022
DOI: 10.1017/s0950268822000176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and imaging features between pulmonary tuberculosis complicated with lung cancer and simple pulmonary tuberculosis: a systematic review and meta-analysis

Abstract: This review aimed to compare the clinical features and CT imaging features between patients with pulmonary tuberculosis (PTB) and lung cancer and patients with PTB alone. That would help to analyze the differences between the two and consequently providing a theoretical basis for the clinical diagnosis and treatment for the patients.Relevant case-control studies focusing on the clinical and CT imaging characteristics between PTB with lung cancer and PTB alone were systematically searched from five electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…20 The study showed no significant difference in most clinical symptoms of the patients in the two groups (persistent chest pain, chest distress, hemoptysis, fever, emaciation, and shortness of breath). 20 Nevertheless, it showed clinical characteristics to differentiate LC and PTB. Irritable cough was found to have a significantly higher frequency in PTB and LC in comparison with PTB only (OR 2.43).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…20 The study showed no significant difference in most clinical symptoms of the patients in the two groups (persistent chest pain, chest distress, hemoptysis, fever, emaciation, and shortness of breath). 20 Nevertheless, it showed clinical characteristics to differentiate LC and PTB. Irritable cough was found to have a significantly higher frequency in PTB and LC in comparison with PTB only (OR 2.43).…”
Section: Discussionmentioning
confidence: 76%
“…Hence, the patients will get proper treatment. 20 The National Cancer Institute found that PTB is associated with an increased risk of LC (odds ratio/OR 2.1, 95% CI 1.4-3.1). PTB was associated with a 1.78fold increased risk of LC in smokers and adenocarcinoma (relative risk: 1.6; 95% CI 1.2-2.1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuberculosis patients have a 50% increased chance of developing LC. Those with a history of tuberculosis for more than 20 years are 2.5 times more likely to develop this disease ( Sun et al, 2022 ). Therefore, these patients must be monitored to prevent the development of this type of cancer, since the prognosis of the disease can also be affected ( Arrieta et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%